(untitled) (Acta Scientiarum. Biological Sciences, 2019)
The application of plant growth regulators can manipulate the development of cultivated plants, and their physiological effects may be reflected in the physiological quality of the seeds. This study evaluated the effects of plant growth regulators (PGR) on the physiological quality of crambe seeds produced in the 2014 and 2015 harvests. During crop development, we applied two foliar sprayings of the following treatments: 1) control treatment with distilled water; 2) indole-3-acetic acid 100 mg L-1 (IAA); 3) 3-gibberellic acid P.A. 100 mg L-1 (GA3); 4) commercial PGR Stimulate® 6 mL L-1. The seeds were harvested and evaluated for water content, germination percentage and germination speed index (GSI), electrical conductivity and concentrations of leached Ca, Mg and K ions. Means were compared by Tukey´s and Dunnett tests (p<0.05). Applying Stimulate® increased the germination percentage and the germination speed index, while IAA application showed an opposite effect, increasing the electrical conductivity of crambe seeds. Calcium leaching decreased with IAA application, and all regulators reduced K leaching. We therefore infer that the application of plant growth regulators influences the physiological quality of crambe seeds.